2015
DOI: 10.1136/heartjnl-2015-307682
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial fibrosis on cardiac magnetic resonance and cardiac outcomes in hypertrophic cardiomyopathy: a meta-analysis

Abstract: LGE is significantly associated with SCD risk, cardiac mortality and all-cause mortality in patients with non-high-risk HCM according to conventional risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(74 citation statements)
references
References 15 publications
1
70
0
3
Order By: Relevance
“…However, it may be due to the small number of mortality events, relatively short follow-up period, or pathophysiological differences such as the prevalence of fibrosis or extent of LV hypertrophy in the studied population. A recent meta-analysis suggested that the presence of LGE was significantly associated with SCD risk, cardiac mortality and all-cause mortality in patients with non-high-risk HCM and that the extent of LGE was not significantly related to the risk of SCD (25). The HCM cohort in the present study may not be representative of the general HCM population, but rather a group with more advanced disease, which may affect the negative findings regarding the relationship between the LVFM and the clinical outcomes.…”
Section: Prognostic Markers Of Hcmmentioning
confidence: 99%
“…However, it may be due to the small number of mortality events, relatively short follow-up period, or pathophysiological differences such as the prevalence of fibrosis or extent of LV hypertrophy in the studied population. A recent meta-analysis suggested that the presence of LGE was significantly associated with SCD risk, cardiac mortality and all-cause mortality in patients with non-high-risk HCM and that the extent of LGE was not significantly related to the risk of SCD (25). The HCM cohort in the present study may not be representative of the general HCM population, but rather a group with more advanced disease, which may affect the negative findings regarding the relationship between the LVFM and the clinical outcomes.…”
Section: Prognostic Markers Of Hcmmentioning
confidence: 99%
“…Several small cohort studies of CMR in HCM have reported an association between the presence of LGE in CMR and worse outcome, including cardiac death and heart failure death, with a trend toward prediction of SCD (pooled OR 2.39, 95 % CI 0.87 to 6.58; p = 0.091) [19]. A more recent meta-analysis including additional studies found a significant association between presence of LGE and SCD events in HCM [20]. In another large, retrospective, multicenter HCM cohort study (n = 1293) followed for 3.3 years after CMR, the amount (defined as the percentage of left ventricular mass with LGE), rather than presence of LGE, was found to be independently associated with SCD events in follow-up.…”
Section: Prognosis and Risk Stratificationmentioning
confidence: 95%
“…36-38 A systemic review including 1,063 HCM patients over a mean follow-up period of 3.1 years showed that LGE had significant prognostic value for all-cause mortality (OR 4.46) and for cardiac death (OR 2.92). 39 More recently, in a meta-analysis of 3,067 patients with HCM during an average follow-up of 3.05 years, 40 the rates of all-cause mortality, sudden cardiac death, and cardiac death in patients with LGE were significantly higher than those in patients without LGE, and LGE was correlated with these adverse outcomes, even in patients with non-high-risk HCM according to conventional risk factors. The results of the present study indicate that the detection of S3 is of importance in the management and risk stratification of patients with HCM, and this is possible using phonocardiography because of its convenience and cost-effectiveness with very few contraindications.…”
Section: Discussionmentioning
confidence: 99%